The “good” and the “bad” subject position in self-injury autobiographies - Gunnarsson, Nina Veetnisha; Lönnberg, Mikaela (Qualitative social work : QSW : research and practice, 2022)
Utilizing published autobiographies, we explore how individuals who self-injure discursively construct their experiences of the self and self-injury. The authors construct their selves into two seemingly opposite subject positions, here named the “bad girl” and the “good girl.” For the most part, the authors identify themselves with the “bad girl” position. Although there is a struggle to uphold normalcy in front of others, they regard evidence of the “good girl” position as fake. We demonstrate how they, to a large extent, accept the dominant discourse of self-injury as an individual and pathological problem for which they tend to blame themselves. However, they also challenge the negative subject position by separating themselves discursively from the bad “side of the self.” Acts of self-injury are described as a way to cope with the negative perception of themselves and at the same time being what causes feelings of self-loathing. Thus, understanding how the psychomedical discourse affects individuals who self-injure as well as the consequences of the medicalization of self-injury are of importance. Furthermore, social workers may be in a legitime position to work with the self-representations and the social factors that may underlie an individual’s need to cut or in other ways physically hurt oneself.